Persuasive Communications, Online Reviews and Service Performances – A Study on the Hotel Industry of New Zealand - Zahir Ahmed; Xinxuan Fan; Mamun Billah (Australasian Accounting, Business and Finance Journal, 2022)
This study examines the relationship between external service quality and hotel performance in New Zealand. Utilising samples consisting of 719 customer reviews from 53 hotels operating under five large hotel chains in major New Zealand tourist cities, it explores how persuasive communication can be linked with the credibility and trustworthiness of online customer feedback and affect the performance of the hotel industry. The SERVQUAL model along with the persuasive communication theory ethos (credibility), logos (reason), and pathos (emotion) are used to measure customer perceptions of the service they receive from top hotel chains, assess the linkage between service performance and profitability, and make suggestions for future research. Customer feedback and ratings from the Trivago website were analysed using a content analysis approach to identify key factors important to customers. This study identifies eleven attributes that are essential to customers as well as to the industry in the service sector, namely, location, rooms, service, cleanliness, value for money, comfort, facilities, buildings, food, WIFI, and parking. The study suggests that there is a significant mediator effect of customer service quality on the interconnected relationship between customer loyalty and hotel performance. The finding provides important information for hotel retail chains that need to promote customer service quality as a vital practice for attracting new customers, as well as for retaining existing customers.
Keywords: Service performances; persuasion; persuasive communication; customer satisfaction; SERVQUAL; value relevance.